Survivin expression in uterine cervical exfoliative cells as diagnostic test of cervical malignancy process - Zulham; Ahmad Aulia Jusuf; Junita Indarti; Lisnawati (Universiti Kebangsaan Malaysia, 2011)
Papanicolaou test is a diagnostic test for uterine cervical cancer screening and routinely examined. It has limitations. A better technique is needed to identify true cervical malignancy process. Molecular cancer marker detection may have high the sensitivity and specificity in detecting cancer. Survivin, a marker candidate, is upregulated in many malignancy processes. Ninety women have joined in this cross sectional study by consecutive sampling. Survivin expression was examined by indirect immunoperoxidase method. It was predominantly found in metaplastic cells. Correlation between survivin expression and Papanicolaou test results was calculated by Fischer’s-exact test. Using Papanicolaou test result as an indicator for the presence of uterine cervical abnormalities, the performance indicators were calculated. Fischer’s-exact test showed that survivin expression was not significantly useful as cervical cancer molecular marker. Survivin expression of the uterine cervical exfoliative cells cannot be used as a diagnostic test for uterine cervical malignancy process.